Long‐term auditory complications after childhood cancer: A report from the Swiss Childhood Cancer Survivor Study. Issue 2 (21st September 2016) - Weiss, Annette; Sommer, Grit; Kasteler, Rahel; Scheinemann, Katrin; Grotzer, Michael; Kompis, Martin; Kuehni, Claudia E.; ,
Abstract: Background: Auditory complications are an adverse event of childhood cancer treatment, especially common in children treated with platinum chemotherapy or cranial radiation. Variation between diagnostic childhood cancer groups has rarely been studied, and we do not know if the burden of auditory complications has changed over the last decades. Procedure: Within the Swiss Childhood Cancer Survivor Study, we sent a questionnaire to all survivors who were diagnosed at age 16 years or less between 1976 and 2005. We compared prevalence of self‐reported hearing loss and tinnitus between all diagnostic childhood cancer groups and siblings, used multivariable logistic regression to analyze the effect of treatment‐related factors on hearing loss, and compared the cumulative incidence of hearing loss between different periods of cancer diagnosis. Results: Prevalence of self‐reported hearing loss was higher in survivors (10%) than in siblings (3%, P < 0.001), and highest in survivors of central nervous system tumors (25%). Significant risk factors were treatment with platinum compounds (carboplatin: odds ratio [OR] 2.4; cisplatin: OR 9.4), cranial radiation (>29 Gy: OR >1.7), or brain surgery (OR 2.2). Children diagnosed in 1986–1995, when platinum compounds came into widespread use, had a significantly higher cumulative incidence of hearing loss than those diagnosed in 1976–1985. In the most recent period, 1996–2005, the risk decreased again, both for patients treated with platinum compounds and with cranial radiation. Conclusions: Our data show that the burden of hearing loss has stabilized in recently treated survivors, suggesting that survivors have benefited from new treatment regimens that use less ototoxic radiation and more carefully dosed platinum compounds.